Transabdominal ultrasonography in preoperative staging of gastric cancer - Liao, Sheng-Ri (World J Gastroenterol, 2004)
AIM: To investigate the value of transabdominal ultrasonography (US) in the preoperative staging of gastric cancer. METHODS: A total of 198 patients with gastric cancer underwent preoperatively transabdominal US, depth of tumor infiltration was assessed in 125 patients, and lymph node metastasis was assessed in 106 patients. RESULTS: The staging accuracy of transabdominal US was 55.6%, 75.0%, 87.3% and 71.1% in T1, T2, T3 and T4 carcinomas, respectively. The overall accuracy was 77.6%. The detection rate for pancreatic invasion and liver invasion was 77.4%, 71.4%, respectively. The sensitivity, specificity, accuracy of transabdominal US in assessment of lymph node metastasis were 77.6%, 64.1%, 72.6%, respectively. Various shapes such as round, ovoid, spindle were encountered in benign and malignant lymph nodes. Majority of both benign and malignant lymph nodes were hyperechoic and had a distinct border. Benign lymph nodes were smaller than malignant lymph nodes in length and width (P = 0.000, 0.005). Irregular shape, fusional shape, infiltrative signs, inhomogenous echo were seen mainly in malignant lymph nodes (P = 0.045, 0.006, 0.027, 0.006). CONCLUSION: Transabdominal US is useful for preoperative staging in gastric cancer, although it is difficult to differentiate benign from malignant lymph nodes.